Poppy and Max and the snow dog - Grindley, Sally; Gardiner, Lindsey (Orchard Books, 2008)
Poppy wants to make a snowdog. Max thinks that looks like hard work. But he soon discovers that being lazy can mean missing out on a lot of fun.